1998
DOI: 10.3109/00048679809062734
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study Comparing Bereavement Phenomena in Recently Bereaved Spouses, Adult Children and Parents

Abstract: Evidence from this study supports the hypothesis that in non-clinical, community-based populations the frequency with which core bereavement phenomena are experienced is in the order: bereaved parents > bereaved spouses > bereaved adult children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 22 publications
7
97
0
2
Order By: Relevance
“…Given evidence that parental grief is the most intense and long-lasting, 2 it was anticipated that symptoms of PGD would be more prevalent in our population than in studies of bereaved spouses or bereaved adult children. In fact, the rate of PGD among parents in our sample was similar to those reported in populations of bereaved individuals following death from natural causes.…”
Section: Discussionmentioning
confidence: 97%
“…Given evidence that parental grief is the most intense and long-lasting, 2 it was anticipated that symptoms of PGD would be more prevalent in our population than in studies of bereaved spouses or bereaved adult children. In fact, the rate of PGD among parents in our sample was similar to those reported in populations of bereaved individuals following death from natural causes.…”
Section: Discussionmentioning
confidence: 97%
“…The scale's authors report high internal consistency (a 5 .92) with a sample of 158 bereaved adults (Burnett et al, 1997). The authors also found evidence for construct validity in that the CBI discriminated between different subsets of the bereaved based on varying levels of grief intensity, which included differentiating between expected and sudden causes of death (Middleton, Raphael, Burnett, & Martinek, 1998). In the current sample, Cronbach's alpha was .94 for the CBI.…”
Section: Methodsmentioning
confidence: 93%
“…Cleiren, Diekstra, Kerkhof, and van der Wal (1994) found that bereaved mothers who had lost a child were the most severely affected group among those who had lost a close person (see also Middleton, Raphael, Burnett, & Martinek, 1998). In a long-term study, Lehman, Wortman, and Williams (1987) found that persons who had lost a child or spouse in an accident had not resolved their grief years after the event.…”
mentioning
confidence: 92%